Introducing minimum wages in Germany: Employment effects in a post Keynesian perspective - Arne Heise; Toralf Pusch (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2018)
There has been a long discussion about the employment impact of minimum wages and this discussion has recently been renewed with the introduction of an economy-wide, binding minimum wage in Germany in 2015. In traditional reasoning, based on the allocational approach of modern labour market economics, it has been suggested that the impact is clearly negative on the assumption of a competitive labour market and clearly positive on the assumption of a monopsonistic labour market. Unfortunately, both predictions conflict with the empirical findings, which do not show a clear-cut impact of significant size in any direction. As an alternative, a Post Keynesian twosector model including an employment market is presented here. Its most likely prediction of a negligible employment effect and a sectoral shift is tested against the German case of an introduction of a statutory minimum wage in 2015. Despite substantial wage increases in the low wage sector, our empirical analysis reveals very low overall employment loss of about 33,000 labourers as a result of a small sectoral shift from low wage industries to higher wage industries.
Keywords: B50; E12; E23; J31; 330; Post Keynesianism; minimum wage; aggregate demand; aggregate supply